A lattice Boltzmann simulation of oblique impact of a single rain droplet on super-hydrophobic surface with randomly distributed rough structures. (7th April 2020) - Shusheng, Zhang; Hao, Lu; Li-Zhi, Zhang; Saffa, Riffat; Zafer, Ure; Huaguan, Zhang
Abstract: In this paper, oblique impact of a single rain droplet on super-hydrophobic surface with randomly distributed rough structures was investigated by lattice Boltzmann method. The effects of the impact angle of the droplet as well as the skewness and kurtosis of rough surface on the bouncing ability of the droplet were in this paper. It was found that the oblique impact can effectively reduce the contact time in the process of droplet bouncing off, because the energy consumption caused by the pinning effect is reduced. Moreover, the contact time most possibly reaches the shortest when the impact angle is 45°. Decreasing the skewness and keeping the kurtosis around 4.0 can enhance the bouncing ability during the droplet oblique impact on randomly distributed rough surfaces. The results are useful for the design of building structures.